Analysis of the Albanian Legislation Related to the Representation of Citizens in the Local Government : Array - Kume, Andon (Journal of Danubian Studies and Research, 2021)
This study analyzes the quality of citizen representation in local government in Albania. The territorial administrative map of Albania contains 61 municipalities and 12 regions. The territory of a municipality lies in urban, peri-urban and rural areas. In them coexist civic communities with different social, economic, cultural, ethnic characteristics, etc. The current legislation provides only the election of the mayor, every four years, according to the majority system with one round and the election of municipal council members according to the proportional system, with closed lists. The lists are proposed by political parties. Independent citizens also have the right to run for mayor or members of the municipal council. Apart from the municipality, for all other territorial-administrative levels, city, neighborhood, administrative unit, village, according to which the municipality is organized, the law on local self-government provides for the establishment of bodies responsible for the administration of local affairs appointed exclusively by the mayor of the municipality. The analysis of the level and quality of the representation of the citizens in the elected local bodies, shows that: (i) the representation in the Municipal Council of the communities living in the urban areas and the rural area is not proportional; (ii) civic communities belonging to marginalized groups are not qualitatively represented; (iii) the representation of national minorities, in particular the Roma and Egyptian minorities, is negligible. The analysis highlights the need for intervention in legislation in order to increase the level of representation and quality of service for local communities, through: (i) election of the administrator and the administration council of the administrative units, every four years, by the citizens; (ii) providing a proportional representation in the municipal council and the regional council of communities residing in urban and rural areas. (iii) providing for the establishment of representation quotas in local elected bodies of national minorities, in accordance with the law on national minorities. The revision of the legal package under which the last territorial-administrative and local self-government reform was implemented, aiming at a comprehensive and consensual legislative process is an effective opportunity to increase the quality of local representative democracy.